Performance improvement of join queries through algebraic signatures. (12th July 2010) - Mokadem, Riad; Hameurlain, Abdelkader; Morvan, Franck
Evaluation of distributed join queries in large scale environments often deals with large data volumes, network with low bandwidth and high number of data sources. Several techniques were proposed to improve join query performances. We propose to combine algebraic signatures with known hash join techniques. Algebraic signatures combined to a semi join based join technique are also very useful for reducing the volume of inter-site transmitted data. We discuss impacts of CPU, I/O and communication costs reductions on the total multi-join query performance improvements. The performance study of our technique shows the reduction of both memory requirements and processing costs especially when the join attribute is a long string. Performances of the semi join based join technique are also significantly improved. We experiment with simple, medium and complex queries in both centralised and distributed environments. Algebraic signatures provide improved performances to reduce significantly communication costs, often the dominant factor in distributed environments.